2021
DOI: 10.1055/s-0041-1730043
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Hyponatremia in Patients Operated for Nonsellar/Suprasellar Supratentorial Tumors—A Prospective Observational Study

Abstract: Background The incidence of hyponatremia is high in supratentorial tumors. However, most studies of supratentorial tumors have included patients with sellar/suprasellar tumors. It is common knowledge that sellar tumors have higher incidence and severity of hyponatremia. Incidence of hyponatremia is not known if we exclude sellar/suprasellar tumors. Therefore, this study was designed to evaluate the incidence of hyponatremia in supratentorial tumors after excluding sellar/suprasellar tumors. Methods After insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Venkatapura et al, 20 reported about 66% incidence of hyponatremia during hospital stay in patients with supratentorial tumors (non-sellar/suprasellar). Moreno et al, 21 reported that the incidence of hyponatremia to be 18% and overall prevalence of water and electrolyte disorders was 30.5% in their study population (n=203).…”
Section: Discussionmentioning
confidence: 99%
“…Venkatapura et al, 20 reported about 66% incidence of hyponatremia during hospital stay in patients with supratentorial tumors (non-sellar/suprasellar). Moreno et al, 21 reported that the incidence of hyponatremia to be 18% and overall prevalence of water and electrolyte disorders was 30.5% in their study population (n=203).…”
Section: Discussionmentioning
confidence: 99%